The Development of a Walkability Audit. Based on Iranian Cities Pedestrian Environment - Soltani, Ali; Hossein Pour, Mohammad; Sholeh, Mahsa; Zare, Parisa (TeMA - Journal of Land Use, Mobility and Environment, 2018)
Given its influence on public health and the vehicle usage and its negative consequences, walkability has attracted much attention in recent decades. Meanwhile, the development of a method to measure walkability of urban areas in order to improve this feature is of utmost importance. Hence, after a comprehensive investigation into environmental measures related to the walking behavior of the users, it was attempted to develop an efficient and reliable environmental audit tool based on these measures. Following the development of a protocol for utilization and management of the tool, two different tests were employed to validate it. The participants were taught how to use the tool, then it was tested in the Eram neighborhood of Shiraz and the results were statistically analyzed. 13 of the environmental measures were found not to have validity to be used in various environments. However, given the remaining 50 items, the tool is valid for being applied to other urban areas.